Balancing Rescue and Realization in the Digital Age: A Global Comparative Analysis of Insolvency Frameworks and the Potential of Artificial Intelligence - Charles Ochieng' Oguk,; Jane Juma, (IJRDO - Journal of Business Management, 2025)
The landscape of insolvency law is characterized by a fundamental tension between two core objectives: enabling the rehabilitation of financially distressed debtors and ensuring the predictable realization of assets for creditors, particularly those holding security interests. Achieving an effective balance is crucial for fostering market confidence, facilitating credit flow, and promoting economic stability. Historically, insolvency regimes have grappled with procedural complexities, systemic inefficiencies, and varied practical outcomes in balancing these competing interests. This article conducts a global comparative analysis of how key jurisdictions, including the United Kingdom, the United States, Singapore, Australia, and Kenya, approach the realization of securities by creditors and debtor rehabilitation within their respective insolvency frameworks. Drawing upon legal research, statutory provisions, case law, and scholarly discourse, it highlights commonalities and divergences in legal mechanisms, judicial approaches, and practical implementation. Furthermore, the article explores the transformative potential of digital technologies and Artificial Intelligence (AI) across the insolvency lifecycle, from pre-insolvency prediction and automated processes to enhanced decision support and efficient asset realization. It examines how AI tools, such as machine learning for prediction, natural language processing for document analysis, and digital platforms for stakeholder interaction, can address existing challenges and enhance the efficiency, predictability, and transparency of insolvency proceedings. The discussion also addresses the critical ethical, regulatory, and practical challenges associated with AI adoption, including issues of data bias, transparency, accountability, privacy, and the need for appropriate human oversight. Ultimately, this paper argues that while legal frameworks provide the foundational balance, digital transformation and the strategic integration of AI are becoming essential instruments to bridge the gap between theoretical objectives and practical outcomes, facilitating a more effective and equitable insolvency ecosystem globally.